The effect of different types of biochar application (Rubber wood saw dust, empty fruit bunch and rice husk) toward rubber seedling growth performance (Hevea brasiliensis) / Aida Adilah Samsudin - Samsudin, Aida Adilah (Faculty of Plantation and Agrotechnology, 2019)
Hevea brasiliensis is one of the major crops planted in Malaysia because the yield produce from rubber tree is widely used across the world. Due to the synthetic rubber production, the demand on natural rubber decreased which caused the decreased of rubber market price. In order to maintain the yield produce, nursery stage of rubber seedling is really important to make sure the seedling can growth healthy when transfer to the field. Biochar is biomass that produced from pyrolysis process as soil condition improve soil fertility. This research was conducted to measure rubber seedling clone PB350 growth performance by using three types of biochar application which are Empty Fruit Bunch (EFB), rice husk, and rubber wood saw dust. Experimental design used in this research is randomized complete block design with three replications. The result from this research indicated that rice husk biochar helps in plant height growth and rubber wood saw dust biochar helps enhanced in stem diameter growth. Both empty fruit bunch biochar and rubber wood saw dust helps in increased number of leafs of rubber seedling.